PROYEKSI DEBIT ALIRAN PERMUKAAN DAS CITARUM BERBASIS LUARAN MODEL ATMOSFER - Sinta Berliana Sipayung; Nani Cholianawati (Lembaga Penerbangan dan Antariksa Nasional, 2011)
Rainfall variability has an impact on the amount of water balance in each watershed (catchment) scale of space and time, so that rainfall variability has an important role to discharge runoff. As the main input is not only rainfall, but the level of land cover and soil physical properties with various concepts was an important input in maintaining the equilibrium amount of water in a watershed, resulting in an equilibrium water balance, and surface flow is considered as a likely output for the sector needs. The data used is the GCM model outputs Geophysical Fluid Dynamics Laboratory (GFDL) in units of rainfall (mm) are reduced from global to local scale. Besides the rainfall data (mm) taken from the Tropical Rainfall Measuring Mission (TRMM, 3B43) satellite with a resolution of 0.25 degrees (equivalent to 27.5 km2), temperature (0C) from the Moderate Resolution Imaging Spectroradiometer (MODIS) level with a resolution of 0.045 degrees (equivalent to 5 km2). Similarly, observational data of rainfall, surface temperature and flow rate (mm3/sec) from 2001 to 2009 are used to validate satellite data and atmospheric models. The correlation between rainfall observations, satellite and atmospheric model outputs are 0.76 and 0.65, respectively. By using the method of Hydrological Simulation Model (HYSIM) can be determined projections of future surface flow atmospheric model based on the DAS Citarum, West Java. Based on the flow rates calculation and observations from 2001 to 2009, have suitability with correlation coefficient of 0.8. The results of calibration flow rate projections from 2011 to 2019 is following the pattern of previous years with a correlation of 0.6. Flow rate is affected by rainfall in the region. Based on the rainfall projections, it is known that rainfall increases with increasing rainfall, the availability of water even more, so that the flow at the surface of the Citarum river basin is expected to increase. Keywords:DAS Citarum, HYSIM, Climate, Satellite, and Atmospheric model